The Walking Classroom: Active Learning Is Just Steps Away!. Issue 2 (12th February 2016) - Becker, Kelly Mancini
Abstract : Walking is a viable and valuable form of exercise for young children that has both physical and mental health benefits. There is much evidence showing that school-age children are not getting the recommended 60 minutes of daily exercise. A school-wide walking program can be a great way to encourage walking in and out of school, can be aligned with the curriculum for educational benefits, and has proven to be a successful motivator. This article describes a variety of walking programs that were developed for schools, which have proven to be fun, motivating and successful.